Implementasi Pembelajaran Berdiferensiasi Berbasis Gaya Belajar Peserta Didik Kelas 7 pada Mata Pelajaran Seni Budaya - Oktiara, Rania Erin; Azizah, Siti Nur; Izzah, Nisda Nabilatul; Naditasari, Rizki Izah; Buwono, Okvito Eka Putu; Artanto, Dhani Febri; Pratamawati, E.W. Suprihatin Dyah (Universitas Negeri Malang, 2024)
This study aimed to describe the implementation of differentiated learning based on learning styles in the Seni Budaya subject for 7th-grade students at SMP Negeri 14 Malang and its impact on student learning outcomes and motivation. Employing a qualitative method with a descriptive approach, the research found that differentiated learning can effectively be applied in 7th-grade classes, positively influencing student outcomes and motivation. The implementation spanned a semester, focusing on artistic creation through a project involving traditional dance performances. Students were grouped based on their kinesthetic, auditory, and visual learning styles, allowing tailored engagement with the material. Kinesthetic learners engaged in hands-on activities, auditory learners in listening exercises and discussions, and visual learners in visual aids utilization. Following the traditional dance performances, comprehensive evaluations were conducted, encompassing both formative and summative assessments. This feedback-oriented evaluation aimed at enhancing student skills and understanding. The differentiated learning approach resulted in increased motivation, improved learning outcomes, and the cultivation of character traits consistent with the Pancasila student profile. In conclusion, this study highlights the efficacy of differentiated learning in enhancing academic performance, motivation, and character development. It offers valuable insights for educators seeking to implement student-centered learning strategies effectively.